JAK-STAT activation contributes to cytotoxic T cell–mediated basal cell death in human chronic lung allograft dysfunction - Aaditya Khatri; Jamie L. Todd; Fran L. Kelly; Andrew Nagler; Zhicheng Ji; Vaibhav Jain; Simon G. Gregory; Kent J. Weinhold; Scott M. Palmer (JCI Insight, 2023)
Chronic lung allograft dysfunction (CLAD) is the leading cause of death in lung transplant recipients. CLAD is characterized clinically by a persistent decline in pulmonary function and histologically by the development of airway-centered fibrosis known as bronchiolitis obliterans. There are no approved therapies to treat CLAD, and the mechanisms underlying its development remain poorly understood. We performed single-cell RNA-Seq and spatial transcriptomic analysis of explanted tissues from human lung recipients with CLAD, and we performed independent validation studies to identify an important role of Janus kinase–signal transducer and activator of transcription (JAK-STAT) signaling in airway epithelial cells that contributes to airway-specific alloimmune injury. Specifically, we established that activation of JAK-STAT signaling leads to upregulation of major histocompatibility complex 1 (MHC-I) in airway basal cells, an important airway epithelial progenitor population, which leads to cytotoxic T cell–mediated basal cell death. This study provides mechanistic insight into the cell-to-cell interactions driving airway-centric alloimmune injury in CLAD, suggesting a potentially novel therapeutic strategy for CLAD prevention or treatment.